Pola Pengasuhan Santri Remaja dalam Memperkuat Budaya Akhlakul Karimah - Syarifah; Nur Hasanah, Muwahidah; Dwi Saputri, Lisa (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
Pesantren is one of the education centers that promotes the values of Islamic law, aiming to form a generation that is ready to fight in accordance with the Qur'an and Hadith. Islamic boarding schools not only provide values education, but are also very effective in shaping children's character. The parenting pattern is a way of providing care to shape the character of the younger generation with good character and strong personalities. However, the current condition of the nation's character often deviates from the values of Pancasila. In an era that lacks morals, Islamic boarding schools are the main solution for parents to educate their children to become noble individuals. Al-Muqoddasah Islamic Boarding School seeks to guide, foster, and educate students to maintain good character. This study aims to analyze the parenting patterns of adolescent students in Islamic character building at Al-Muqoddasah Islamic Boarding School in Ponorogo. This research uses descriptive qualitative methods with data collection techniques through observation, interviews, and documentation. Data analysis includes data reduction, data presentation, and data verification. The results showed that the parenting pattern at Al-Muqoddasah Islamic Boarding School applies democratic parenting through direction, training, assignment, habituation, supervision, and uswatun hasanah. Special programs every Monday night, such as the study of fiqh, hadith, mahfudzot, as well as tausyiah from senior teachers and seminars, support the formation of Islamic character. Supporting factors include role modeling, motivation, and a good environment while inhibiting factors include activities, friends, parents, intention to enter the hut, and emotional instability